Local discourse, identity and the search for a Filipino philosophy a re-exploration throgh the lens of Reynaldo Ileto - Abellanosa, Rhoderick John S. (2013)
Working within the framework of Reynaldo Ileto’s postcolonial discourse, this paper re-explores the Filipino philosophy question and its contem- porary relevance. Re-exploration in this context means re-reading and arguing for sustained discussions on Filipino philosophy. Divided into three parts, the paper presents the history and development of the Filipino philosophy debate and proceeds to an analysis and reflection on Ileto’s writing from Pasyon and Revolution to his more recent work. The third and final part proposes a rethinking of what has been identi- fied as Filipino philosophy in the light of Ileto’s ideas. At the core of this endeavor is the contention that a culture-grounded philosophy is indispensable in nationhood and state-formation. Thus, whether it shall be called “philosophies in the Philippines” or “Filipino philosophy,” or whatever possible nomenclature for such an endeavor, the most es- sential thing is that Filipinos consciously identify and shape their own discourse as a people. Finally, this paper argues for the relevance of continually discussing the question concerning Filipino philosophy.
Keywords: Filipino philosophy; Political philosophy; Postcolonialism